Staging of Alzheimer's disease: past, present, and future perspectives. Issue 9 (September 2022) - Therriault, Joseph; Zimmer, Eduardo R.; Benedet, Andrea L.; Pascoal, Tharick A.; Gauthier, Serge; Rosa-Neto, Pedro
Abstract : For many years Alzheimer's disease (AD) was associated with the dementia stage of the disease, the tail end of a pathophysiological process that lasts approximately two decades. Whereas early disease staging assessments focused on progressive deterioration of clinical functioning, brain imaging with positron emission tomography (PET) and cerebrospinal fluid (CSF) biomarker studies highlighted the long preclinical phase of AD in which a cascade of detectable biological abnormalities precede cognitive decline. The recent proliferation of imaging and fluid biomarkers of AD pathophysiology provide an opportunity for the identification of several biological stages in the preclinical phase of AD. We discuss the use of clinical and biomarker information in past, present, and future staging of AD. We highlight potential applications of PET, CSF, and plasma biomarkers for staging AD severity in vivo . Highlights: Disease staging uses important points in the disease course to measure disease severity, evaluate clinical outcomes, and guide patient management. Staging of Alzheimer's disease (AD) has evolved from clinically defined stages based on symptomatic severity to integrated information on several biomarkers. Currently, staging of AD involves the identification of AD using biomarkers, with clinical outcomes designating disease severity. Staging of preclinical AD is possible using imaging biomarkers optimized to detect stage-specific pathological changes. Furthermore, phosphorylated tau (pTau) panels in which multiple pTau epitopes are evaluated from a single sample (plasma or CSF) may be useful for determining the extent of pathological tau hyperphosphorylation. Staging of AD using biomarkers will allow the identification of the optimal time-window in which specific therapeutic interventions will be most effective.